2021
DOI: 10.3390/antiox10111760
|View full text |Cite
|
Sign up to set email alerts
|

Novel Photoinduced Squalene Cyclic Peroxide Identified, Detected, and Quantified in Human Skin Surface Lipids

Abstract: Skin surface lipids (SSLs) form the first barrier that protects the human organism from external stressors, disruption of the homeostasis of SSLs can result in severe skin abnormalities. One of the main causes of this disruption is oxidative stress that is primarily due to SSLs oxidation. Squalene (SQ), the most abundant lipid among SSLs, was shown to first undergo singlet molecular oxygen (1O2) oxidation to yield 6 SQ-monohydroperoxide (SQ-OOH) isomers as the primary oxidation products. However, due to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…Quantum chemical calculations of NMR chemical shifts and coupling constants have been extensively utilized to confirm proposed structures or to aid reassignment of structures [ 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 ]. Nevertheless, in the field of free fatty acids and their hydroperoxide derivatives, only a limited number of computational studies have so far been reported [ 112 , 138 , 141 , 155 , 156 ]. Recently, Venianakis et al [ 112 ] presented a density functional theory (DFT) study of the 1 H- and 13 C-NMR chemical shifts of the geometric isomers of 18:2 ω-7-conjugated linoleic acid (CLA) and nine model compounds, using five functionals and two basis sets.…”
Section: Structural Investigations Based On Quantum Chemical Calculat...mentioning
confidence: 99%
See 3 more Smart Citations
“…Quantum chemical calculations of NMR chemical shifts and coupling constants have been extensively utilized to confirm proposed structures or to aid reassignment of structures [ 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 ]. Nevertheless, in the field of free fatty acids and their hydroperoxide derivatives, only a limited number of computational studies have so far been reported [ 112 , 138 , 141 , 155 , 156 ]. Recently, Venianakis et al [ 112 ] presented a density functional theory (DFT) study of the 1 H- and 13 C-NMR chemical shifts of the geometric isomers of 18:2 ω-7-conjugated linoleic acid (CLA) and nine model compounds, using five functionals and two basis sets.…”
Section: Structural Investigations Based On Quantum Chemical Calculat...mentioning
confidence: 99%
“…Quantum chemical calculations of NMR parameters have also been extensively used for the precise determination of diastereomerism of natural products with multiple asymmetric centers [ 138 , 141 , 142 , 143 , 158 , 159 , 160 , 161 ]. On the contrary, in the field of lipid hydroperoxides, only three papers have so far been reported [ 138 , 141 , 156 ]. It has been demonstrated that the oxidation of methyl linolenate results in the formation of four peroxyl radicals which lead to conjugated dienoic 9-, 12-, 13-, and 16-hydroperoxides [ 10 , 98 , 139 , 162 ] ( Figure 48 ).…”
Section: Structural Investigations Based On Quantum Chemical Calculat...mentioning
confidence: 99%
See 2 more Smart Citations
“…[31] In the last few decades, a great effort has been made to compute NMR parameters to confirm proposed structures or to aid reassignment of structures [33][34][35][36][37][38][39][40][41][42][43][44] and to investigate the effects of solvents on molecular structures. [26,37,40,[44][45][46] To date, however, only a handful examples of NMR computational studies of fatty acids [47][48][49] and their hydroperoxide derivatives [31,50] have been published. We report herein detailed DFT calculations of δ( 13 C) and δ( 1 H) chemical shifts and 3 J ( 13 C O O 1 H) coupling constants as structural tools of model hydroperoxides and provide a critical evaluation of the prospects and limitations of 1 H 13 C HMBC experiments in the analysis of hydroperoxide moieties.…”
Section: Introductionmentioning
confidence: 99%